Discourses of Ageing and Gender The Impact of Public and Private Voices on the Identity of Ageing Women - Anderson, Clare; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book presents in-depth investigation of the language used about women and ageing in public discourse, and compares this with the language used by women to express their personal, lived experience of ageing. It takes a linguistic approach to identify how messages contained in public discourse influence how individual women evaluate their own ageing, and particularly their ageing appearance. It begins by establishing the wider cultural context that produces prevailing attitudes to women, before turning to an analysis of representations of the ageing female body in beauty and cosmetic advertising and the lifestyle media. The focus then moves to a detailed investigation of women's own perceptions of the process of ageing and of their ageing appearance as revealed through their personal narratives. The final chapters challenge dominant attitudes to women and ageing by presenting two case studies of women who for different reasons and in different waysrefuse to conform to cultural expectations. This work provides a platform for further academic research in the fields of linguistics, gerontology, gender and media studies; as well as offering meaningful applications in the wider domains of business and advertising. Clare Anderson is Associate Tutor at the University of Birmingham, UK. She also runs a consultancy that specialises in helping individuals, companies and brands to use language to perform more effectively. Her work focuses on women and leadership, and language and diversity.
Chapter One: Introduction -- Chapter Two: Cultural Context -- Chapter Three: Analytic Frameworks -- Chapter Four: Public Voices: Skincare Advertising And Discourses Of "Beauty" -- Chapter Five: Public Voices: The Media Mirror -- Chapter Six: Private Voices: Talking About Ageing -- Chapter Seven: Private Voices: Ageing In The Mirror -- Chapter Eight: Transgressive Women: Celebration And Censure -- Chapter Nine: Conclusions And Implications.
Keywords: Sociolinguistics; Sex; Aging; Linguistics -- Methodology; Feminism; Feminist theory; Sociolinguistics; Gender Studies; Ageing; Research Methods in Language and Linguistics; Feminism and Feminist Theory